Semen sampling as a simple, noninvasive surrogate for prostate health screening. (3rd September 2021) - Lorente, Gisela; Ntostis, Panagiotis; Maitland, Norman; Mengual, Lourdes; Musquera, Mireia; Muneer, Asif; Oliva, Rafael; Iles, David; Miller, David
ABSTRACT: The detection rates for prostate cancer (pCa) by invasive biopsy are high, fully justifying its use in confirmatory testing. False-positive results of prior, relatively insensitive screening tests, however, can lead to expensive and often unnecessary surgery. Several reports have suggested the potential use of the ejaculate to screen for prostate conditions. Hitherto, the potential impact of sterilization on the diagnostic potential of seminal plasma screening has not been examined. Herein, we report cellular and molecular comparisons of semen samples obtained from normal (N = 5), vasectomized (N = 5) and prostate pathology patients (N = 4; confirmed by a biopsy) that were centrifuged over 60% PureSperm cushions. Non-penetrating cells were washed prior to immunocytochemistry with prostatic epithelial cell markers including PSMA, NKX3.1 and CD24. KRT18 was used to highlight epithelial cells in these samples. RNA sequencing was then used to identify differentially expressed small RNAs associated with vasectomy and prostate pathology. Specific gene transcripts were confirmed by RT-qPCR. PMSA + /KRT18 +, CD24 + /KRT18 + and NKX3.1/ + KRT18 + cells were observed, albeit infrequently in most processed semen samples by indirect immunocytochemistry. Targeted RT-qPCR supported their enrichment, along with their putative designation as prostatic luminal cells. Small RNAs in seminal plasma were highly heterogeneous, with tRNAs and miRNAs being the dominant forms. Hsa-miR-143 and hsa-miR-199 were among the most prominent of the differentially expressed miRNAs upregulated in samples with prostate pathology but not vasectomy. The targets of these small RNAs illustrate biological processes involved among others in transcription regulation and collagen metabolism. Our outcomes strongly support an appraisal of selected biologically meaningful small RNAs of ejaculate semen for prostate health screening. A long-term goal would be a simple, routine, noninvasive test for monitoring prostate health, potentially among younger men.